2023
DOI: 10.1002/adhm.202203411
|View full text |Cite
|
Sign up to set email alerts
|

A Bioinspired Gelatin–Amorphous Calcium Phosphate Coating on Titanium Implant for Bone Regeneration

Abstract: Biocompatible and bio‐active coatings can enhance and accelerate osseointegration via chemical binding onto substrates. Amorphous calcium phosphate (ACP) has been shown as a precursor to achieve mineralization in vertebrates and invertebrates under the control of biological macromolecules. This work presents a simple bioinspired Gelatin‐CaPO4 (Gel‐CaP) composite coating on titanium surfaces to improve osseointegration. The covalently bound Gel‐CaP composite is characterized as an ACP‐Gel compound via SEM, FT‐I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 75 publications
0
4
0
Order By: Relevance
“…47 In addition, the ratio of nanohardness ( H ) to Young's modulus (elastic modulus, E ) was calculated to evaluate the elastic strain of coating failure. 48 The H / E values of Ti@PDA-NOate/CuS were higher than Ti (0.016 compared to 0.013, respectively), indicating that Ti@PDA-NOate/CuS may have better wear resistance.…”
Section: Resultsmentioning
confidence: 88%
“…47 In addition, the ratio of nanohardness ( H ) to Young's modulus (elastic modulus, E ) was calculated to evaluate the elastic strain of coating failure. 48 The H / E values of Ti@PDA-NOate/CuS were higher than Ti (0.016 compared to 0.013, respectively), indicating that Ti@PDA-NOate/CuS may have better wear resistance.…”
Section: Resultsmentioning
confidence: 88%
“…1 a) demonstrated the homogeneous and porous network microstructure of the obtained pTi prosthesis. The interconnected microstructure would benefit cell penetration and nutrient transport, promoting angiogenesis and induce bone ingrowth [ 33 , 34 ]. Besides, the microstructure increased the surface roughness and specific surface area to enhance the prosthesis–bone interaction and initial stability, so that the micro-movements at the interface could be minimized.…”
Section: Resultsmentioning
confidence: 99%
“…137 Experiments utilizing various types of cells including human mesenchymal stem cells and osteoblast-like cells have demonstrated that CaP coatings promote cellular attachment, growth, and specialization, thereby promoting bone regeneration. 138,139 Building upon this foundation, the field of research now focuses on biofunctional hybrid composite CaP coatings containing both inorganic CaP coating and organic elements designed to stimulate tissue growth and promote the formation of blood vessels. To further explore the therapeutic outcomes of hybrid calcium phosphate coatings, various studies have investigated the impacts of implanted material design, surgical procedure, and coating characteristics ( e.g.…”
Section: Artificial Biomaterialsmentioning
confidence: 99%